A secure and efficient multi cloud-based data storage and retrieval using hash-based verifiable secret sharing scheme. (4th January 2021) - Farhadi, Majid; Bypour, Hamideh; Asadi, Seyyed Erfan
As the availability of many smart devices rises, fast and easy access to data as well as sharing more information is felt. Cloud computing is a computational approach that shares configurable resources such as network, servers, storage space, applications and services on the internet. The confidentiality, integrity, and availability of the data, reducing computational cost and communication channel between the data owner and cloud service providers are essential parts of cloud computing. In the paper, we propose a new scheme to construct a secure cloud data storage based on the verifiable secret sharing scheme with public verifiability to protect data integrity. And the verification phase does not depend on any computational assumptions. The proposed scheme cannot only detect the cheating but also identify who are the cheaters. It is worth noting that the proposed scheme is more efficient compared with the other secret sharing-based cloud data storage since heavy and complex computation is not required.